2012
DOI: 10.1128/mcb.00547-12
|View full text |Cite
|
Sign up to set email alerts
|

Mus81-Mms4 Functions as a Single Heterodimer To Cleave Nicked Intermediates in Recombinational DNA Repair

Abstract: The formation of crossovers is a fundamental genetic process. The XPF-family endonuclease Mus81-Mms4 (Eme1) contributes significantly to crossing over in eukaryotes. A key question is whether Mus81-Mms4 can process Holliday junctions that contain four uninterrupted strands. Holliday junction cleavage requires the coordination of two active sites, necessitating the assembly of two Mus81-Mms4 heterodimers. Contrary to this expectation, we show that Saccharomyces cerevisiae Mus81-Mms4 exists as a single heterodim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
57
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 61 publications
9
57
1
Order By: Relevance
“…In relation to a stalled fork, this would allow unwinding of the lagging strand, potentially generating a substrate for MUS81. However, the precise substrate recognized by MUS81 at the fork is not known, but possibilities include Holliday junctions generated by replication fork regression or the stalled fork itself 8,21,22 . Our data on the role of MUS81 in the response to HU are in agreement with Hanada et al 6 with regard to MUS81-induced DNA DSB formation.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to a stalled fork, this would allow unwinding of the lagging strand, potentially generating a substrate for MUS81. However, the precise substrate recognized by MUS81 at the fork is not known, but possibilities include Holliday junctions generated by replication fork regression or the stalled fork itself 8,21,22 . Our data on the role of MUS81 in the response to HU are in agreement with Hanada et al 6 with regard to MUS81-induced DNA DSB formation.…”
Section: Discussionmentioning
confidence: 99%
“…S2). Perhaps our inability to cytologically detect MUS81 is related to the observation that Mus81-Mms4 acts as a single heterodimer (25), whereas Mlh1 appears to have a structural role also (26). Regardless, in the absence of an effective antibody to MUS81 protein, we classified and mapped RNs from nuclei in which each of the twelve chromosomes had at least one MLH1 focus to minimize the chance that an RN was not labeled with MLH1 antibodies for technical reasons (see SI Appendix, SI Materials and Methods for details and tests of selection criteria).…”
Section: Resultsmentioning
confidence: 99%
“…PLK1 and orthologs in yeast (S. cerevisiae Cdc5) have also been shown to regulate the activation of MUS81-EME1 and stimulate its association with the SLX4-endonuclease complex (Matos et al 2011;Gallo-Fernandez et al 2012;Munoz-Galvan et al 2012;Schwartz et al 2012;Szakal and Branzei 2013). Although it is not clearly essential for fork collapse in all cell types, the Mus81-Eme1 complex in Schizosaccharomyces pombe plays a crucial role in DSB generation at stalled replication forks (Froget et al 2008), and a similar relationship has been observed in mammalian cells when CHK1 is inhibited (Forment et al 2011).…”
mentioning
confidence: 89%